1-Methyl-tryptophan synergizes with methotrexate to alleviate arthritis in a mouse model of arthritis. (September 2014) - Pigott, Elizabeth; DuHadaway, James B.; Muller, Alexander J.; Gilmour, Susan; Prendergast, George C.; Mandik-Nayak, Laura
Abstract Rheumatoid arthritis (RA) is an inflammatory autoimmune disease with no known cure. Current strategies to treat RA, including methotrexate (MTX), target the later inflammatory stage of disease. Recently, we showed that inhibiting indoleamine-2, 3-dioxygenase (IDO) with 1-methyl-tryptophan (1MT) targets autoantibodies and cytokines that drive the initiation of the autoimmune response. Therefore, we hypothesized that combining 1MT with MTX would target both the initiation and chronic inflammatory phases of the autoimmune response and be an effective co-therapeutic strategy for arthritis. To test this, we used K/BxN mice, a pre-clinical model of arthritis that develops joint-specific inflammation with many characteristics of human RA. Mice were treated with 1MT, MTX, alone or in combination, and followed for arthritis, autoantibodies, and inflammatory cytokines. Both 1MT and MTX were able to partially inhibit arthritis when used individually; however, combining MTX + 1MT was significantly more effective than either treatment alone at delaying the onset and alleviating the severity of joint inflammation. We went on to show that combination of MTX + 1MT did not lower inflammatory cytokine or autoantibody levels, nor could the synergistic co-therapeutic effect be reversed by the adenosine receptor antagonist theophylline or be mimicked by inhibition of polyamine synthesis. However, supplementation with folinic acid did reverse the synergistic co-therapeutic effect, demonstrating that, in the K/BxN model, MTX synergizes with 1MT by blocking folate metabolism. These data suggest that pharmacological inhibition of IDO with 1MT is a potential candidate for use in combination with MTX to increase its efficacy in the treatment of RA.